(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2013)
The aim of the present work, which is the result of a research project intended to define and design a new concept of architectural - sculptural objects, analyzing the historical and contemporary links, comparing and classifying three-dimensional objects with plastic values adapted for this study, allowed to establish differences and similarities both in architectural and sculptural works, obtaining a classification that allows to establish specific categories for future investigations. The study has a descriptive character, classified as a correlational investigation, determining the relations between the architecture and the sculpture through form and function as fundamental elements between them.